Pamudi Media Assisted by Index Card Match: An Innovative Science Learning Effort to Strengthen Students' Cooperation Character - Rahmawati, Isna Rizkita; Untari, Esti; Surayanah, Surayanah (Proceedings Series of Educational Studies, 2024)
Science learning in schools is synonymous with students' learning process skills, which include critical thinking and reasoning, as well as cooperation and respect for the opinions of others. The selection of learning media is necessary to meet the learning needs of students by providing meaningful learning experiences. The purpose of this research and development is to develop PAMUDI media "Puzzle Dua Sisi" supported by index card match on the material form of objects and changes in the form of objects to strengthen cooperation in grade IV students that are valid, practical and interesting. The findings show that science learning at SDN Pohkecik and SDN Sumberkarang is done in a monotonous pattern, resulting in less interaction among students, and boredom appears in students. Therefore, media is needed to make the learning process more varied. The research method used is the ADDIE method. Data collection techniques were carried out through observation, interviews and distribution of questionnaires. The results obtained from the research and development of PAMUDI media in the form of a validity test of 91.65% with a very valid category, a practicality test of 100% with a very practical category, and user attractiveness of 96.9% with a very attractive category, as well as the ability of the media to strengthen the character of cooperation 95.45% with a category very capable of strengthening the character of student cooperation.